Fostering Culturally Relevant Teaching Through Family Visits - Szech, Laura (International Journal of Multicultural Education, 2022)
This study examines if teachers can learn to be more culturally relevant in their classrooms by reading culturally relevant literature and then engaging in the practice of family visits. The study employed a basic qualitative design with data sources such as transcripts of discussions and visits, interviews, and participant journals. Results show that family visits led to new and more culturally relevant classroom practices. Based on this study, teachers who engage with culturally relevant training, including the practice of family visits, may become more culturally relevant in their classrooms.